2016
DOI: 10.1038/srep37152
|View full text |Cite
|
Sign up to set email alerts
|

Two PTP receptors mediate CSPG inhibition by convergent and divergent signaling pathways in neurons

Abstract: Receptor protein tyrosine phosphatase σ (PTPσ) and its subfamily member LAR act as transmembrane receptors that mediate growth inhibition of chondroitin sulfate proteoglycans (CSPGs). Inhibition of either receptor increases axon growth into and beyond scar tissues after CNS injury. However, it is unclear why neurons express two similar CSPG receptors, nor whether they use the same or different intracellular pathways. We have now studied the signaling pathways of these two receptors using N2A cells and primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 112 publications
(159 reference statements)
1
62
0
Order By: Relevance
“…(E)]. CSPGs also decrease Erk signaling (Ohtake et al, ). However, inhibition of Mek‐Erk signaling using PD325901 (1 μ M , 1 h) also did not affect either Mito‐Tip ( p = 0.75, n = 166 and 144) or the number of mitochondria in growth cones ( p = 0.97) on the control substratum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(E)]. CSPGs also decrease Erk signaling (Ohtake et al, ). However, inhibition of Mek‐Erk signaling using PD325901 (1 μ M , 1 h) also did not affect either Mito‐Tip ( p = 0.75, n = 166 and 144) or the number of mitochondria in growth cones ( p = 0.97) on the control substratum.…”
Section: Resultsmentioning
confidence: 99%
“…The LAR receptor inhibits PI3K and Erk signaling and activates RhoA‐ROCK (Fisher et al, ; Ohtake et al, ) and is localized to the growth cones of the chicken sensory neurons used in this study (Ketschek et al, ). The data indicate a sufficient and necessary role for suppression of PI3K signaling, but not ROCK or Erk, downstream of LAR in the effects of CSPGs on mitochondria positioning at growth cones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NPCs, we found that ROCK inhibition allows NPCs to grow on CSPGs and promote their survival and oligodendrogenesis (Dyck et al, ). Similarly, genetic knockdown approaches have implicated both LAR and PTPσ in mediating Rho activation in primary cerebellar granule neurons (Ohtake, Wong, Abdul‐Muneer, Selzer, & Li, ). Notably, Rho activation has been associated with p75‐mediated apoptosis in neurons and glial cells (Dubreuil et al, ); however, its link to LAR and PTPσ has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In NPCs, we found that ROCK inhibition allows NPCs to grow on CSPGs and promote their survival and oligodendrogenesis . Similarly, genetic knockdown approaches have implicated both LAR and PTPσ in mediating Rho activation in primary cerebellar granule neurons (Ohtake, Wong, Abdul-Muneer, Selzer, & Li, 2016).…”
Section: Ilp and Isp Promote Endogenous Cell Proliferation And Oligmentioning
confidence: 99%